Garcinia yaatapsap (Clusiaceae), a new species from northern Myanmar - Sweeney, Patrick W.; Nwe, Thet Yu; Armstrong, Kate E. (Phytotaxa, 2022)
Garcinia yaatapsap (Clusiaceae), a new species from northern Myanmar, is described and illustrated. The new species is most similar to G. stipulata and G. nujiangensis, but differs primarily by its subsessile, subcordate to cordate leaves and strongly angled branchlets (versus petiolate, cuneate leaves and terete branches in G. stipulata and G. nujiangensis).